2014
DOI: 10.1080/21551197.2014.927303
|View full text |Cite
|
Sign up to set email alerts
|

Keeping Consumers Safe: Food Providers' Perspectives on Pureed Food

Abstract: Twelve focus groups were conducted in five sites with 80 allied health providers to identify their perspectives on providing pureed food to consumers. Thematic care analysis was completed to summarize and interpret these data. Providers' greatest concern was keeping consumers safe, and the right texture was prioritized over sensory appeal and acceptance. Providers recognized that these foods impacted the quality of life of consumers and worked to rationalize these diets with residents/patients and their famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Previous research revealed that the intake of texture-modified diets usually lack appearance and taste [29] and are accompanied by lower energy and protein intake compared to usual meals [30]. Therefore, we reshaped the texture-modified diet.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research revealed that the intake of texture-modified diets usually lack appearance and taste [29] and are accompanied by lower energy and protein intake compared to usual meals [30]. Therefore, we reshaped the texture-modified diet.…”
Section: Discussionmentioning
confidence: 99%
“…Carers’ beliefs that modified diets are unpalatable also contribute to non-compliance. In a recent study of staff perceptions of pureed food, most had a negative view describing such food with terms like ‘tasteless’ and ‘mush’; positive comments such as ‘tasty’ and ‘aromatic’ mainly came from allied health professionals and dietary-nutrition staff [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apply the International Dysphagia Diet Standardization Initiative framework in the prescription, preparation, and assessment of TMDs and thickened liquids to facilitate consistent communication between nursing home staff, carers, and professionals, and reduce variability in the preparation, assessment, and prescription of TMDs and thickened liquids (41).…”
Section: Tablementioning
confidence: 99%